Adapting gastrointestinal organoids for pathogen infection and single cell sequencing under biosafety level 3 (BSL-3) conditions - Stanifer, Megan; Boulant, Steeve (JoVE. Video journal, 2021)
Human intestinal organoids constitute the best cellular model to study pathogen infections of the gastrointestinal tract. These organoids can be derived from all sections of the GI tract (gastric, jejunum, duodenum, ileum, colon, rectum) and, upon differentiation, contain most of the cell types that are naturally found in each individual section. For example, intestinal organoids contain nutrient-absorbing enterocytes, secretory cells (Goblet, Paneth, and enteroendocrine), stem cells, as well as all lineage-specific differentiation intermediates (e.g., early or immature cell types). The greatest advantage in using gastrointestinal tract-derived organoids to study infectious diseases is the possibility of precisely identifying which cell type is targeted by the enteric pathogen and to address whether the different sections of the gastrointestinal tract and their specific cell types similarly respond to pathogen challenges. Over the past years, gastrointestinal models, as well as organoids from other tissues, have been employed to study viral tropism and the mechanisms of pathogenesis. However, utilizing all the advantages of using organoids when employing highly pathogenic viruses represents a technical challenge and requires strict biosafety considerations. Additionally, as organoids are often grown in three dimensions, the basolateral side of the cells is facing the outside of the organoid while their apical side is facing the inside (lumen) of the organoids. This organization poses a challenge for enteric pathogens as many enteric infections initiate from the apical/luminal side of the cells following ingestion. The following manuscript will provide a comprehensive protocol to prepare human intestinal organoids for infection with enteric pathogens by considering the infection side (apical vs. basolateral) to perform single-cell RNA sequencing to characterize cell-type-specific host/pathogen interactions. This method details the preparation of the organoids as well as the considerations needed to perform this work under biosafety level 3 (BSL-3) containment conditions.
Enthält auch Textversion
Gesehen am 11.12.2021
Wissenschaftlicher Film. Deutschland. 2021
Keywords: Film